Meat yield to total weight relationship in freshwater giant prawn Macrobrachium rosenbergii - Haq, M E; Quddus, M A (Indian Journal of Fisheries, 2011)
Information on the meat yield in relation to total weight in freshwater giant pmwn is important to both farmers and consumers in respect of marketing and processing aspects, but no report is available in this regard. The present study was undertaken to determine the changes in the meat yield to increasing total weight including carcass composition and length-weight relationship of Macrobrachium rosenbergii.